Localized movement and morphology of UBF1-positive nucleolar regions are changed by γ-irradiation in G2 phase of the cell cycle - Sorokin, Dmitry V; Stixová, Lenka; Sehnalová, Petra; Legartová, Soňa; Suchánková, Jana; Šimara, Pavel; Kozubek, Stanislav; Matula, Pavel; Skalníková, Magdalena; Raška, Ivan; Bártová, Eva (Nucleus, 2015)
The nucleolus is a well-organized site of ribosomal gene transcription. Moreover, many DNA repair pathway proteins, including ATM, ATR kinases, MRE11, PARP1 and Ku70/80, localize to the nucleolus (Moore et al., 2011 ). We analyzed the consequences of DNA damage in nucleoli following ultraviolet A (UVA), C (UVC), or γ-irradiation in order to test whether and how radiation-mediated genome injury affects local motion and morphology of nucleoli. Because exposure to radiation sources can induce changes in the pattern of UBF1-positive nucleolar regions, we visualized nucleoli in living cells by GFP-UBF1 expression for subsequent morphological analyses and local motion studies. UVA radiation, but not 5 Gy of γ-rays, induced apoptosis as analyzed by an advanced computational method. In non-apoptotic cells, we observed that γ-radiation caused nucleolar re-positioning over time and changed several morphological parameters, including the size of the nucleolus and the area of individual UBF1-positive foci. Radiation-induced nucleoli re-arrangement was observed particularly in G2 phase of the cell cycle, indicating repair of ribosomal genes in G2 phase and implying that nucleoli are less stable, thus sensitive to radiation, in G2 phase.
Keywords: záření gama; Animals; DNA Damage; apoptóza; Gamma Rays; buněčné linie; Cell Line, Tumor; Apoptosis; Cell Cycle; G2 fáze; transkripční iniciační komplex Pol1 - proteiny; Cell Nucleolus; Transcription, Genetic; Mice; Pol1 Transcription Initiation Complex Proteins; Ultraviolet Rays; myši; Cell Line; buněčný cyklus; Computational Biology; genetická transkripce; G2 Phase; poškození DNA; zvířata; výpočetní biologie; buněčné jadérko; nádorové buněčné linie; ultrafialové záření